COMPLEX FOR ELEMENTAL ANALYSIS OF SUBSURFACE LAYERS WITH NANOMETER DEPTH RESOLUTION - A. S. Kamyshan; F. F. Komarov; V. V. Danilevich; P. A. Grishan (Приборы и методы измерений)
A measuring complex for quantitative analysis of element contents and distributions of doping atoms in subsurface layers of crystals as well as in thin films by means of the registration of energy spectra of ions scattered to angles higher than π/2 has been designed and fabricated. The complex construction is based on a module-bloc principle. This complex includes microcontrollers which enables us to shorten elemental base of these devices. The measured energy resolution amounts to 1,3 %, energy width of one channel amounts to 281 eV, a range of registered energies amounts 37 to 281 keV, and method sensitivity amounts to 5x1014 at/cm2 .